Terapkan Safetyplay untuk Mencegah Bahaya pada Anak Usia Dini saat Bermain Playground - Salsabila Fitrian; Ismaniar Ismaniar; Llili Dasa Putri (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2025)
Playgrounds have an important role in supporting early childhood development (AUD) holistically, including physical, cognitive, social and emotional aspects. As a space for exploration and play, playgrounds are designed to stimulate children's gross and fine motor skills, creativity, problem solving and social skills. However, safety is the main factor that must be considered when designing a playground. The safety play concept is applied to minimize the risk of physical injury and psychological trauma to children while playing. Implementation of safety play includes the use of safe surface materials, play equipment according to safety standards, adult supervision, separation of areas based on age groups, and safety education for children. With a safe and functional design, playgrounds not only provide a sense of security for children but also support their optimal development. This research highlights the importance of playgrounds as a means of learning and developing AUD as well as examining the application of safety play to create an ideal playing environment.